SISTEM DAN PROSEDUR PENGAJUAN KEBERATAN DAN BANDING PAJAK BUMI DAN BANGUNAN DI KOTA BANJARBARU - Ansyari, Muhammad Hafiz; Lili Safrida; Ali Sadikin (Universitas Lambung Mangkurat, 2022)
This research aims to determine the system and procedures for submitting objections and appeals to Land and Building Tax in Banjarbaru City. This research was conducted at the Banjarbaru City Regional Tax and Levy Management Agency office. The type of data taken and used in this research is qualitative data. The results of the research are that the factors that cause PBB objections are that taxpayers feel that the SPPT/SKP does not correspond to the actual situation, regarding the area, classification or imposition of land and building tax objects. The factors that cause a PBB objection application to be granted, granted in part, rejected, namely whether the objection letter is submitted is justified or not, the results of the research show things that are in accordance with the reasons for the objection request or not and the taxpayer can prove the untruth of the tax assessment letter ex officio or not. The procedures for submitting objections and appeals for land and building tax are in accordance with the Standard Operating Procedures established at the Regional Revenue and Asset Financial Management Agency.